Demyelinating polyneuropathy, dermatomyositis, and interstitial pneumonitis associated with autoantibody against melanoma differentiation-associated gene 5 - Yu-Hsiang Chiu (Journal of Medical Sciences, 2017)
Patients with serum anti-melanoma differentiation-associated gene 5 autoantibodies (anti-MDA5) are related to amyopathic dermatomyositis, especially in Asians. Here, we present a 46-year-old woman who was diagnosed with anti-MDA5-mediated demyelinating polyneuropathy clinically mimicking dermatomyositis. She had rapid progression of interstitial pneumonitis complicated with Pneumocystis jirovecii and Aspergillus pneumonia with septic shock. It is rare that patients with anti-MDA5-positive dermatomyositis present as demyelinating polyneuropathy.